Moving Towards Sustainability: Environmental Management Strategies and Sustainable Infrastructures Development at Universidad Catolica de Córdoba (UCC) - Perfumo, Maria Soledad; Ferraresi, Leonela; Imhof, Lelia (Journal of Sustainability Perspectives, 2024)
This study focuses on the "Setting and Infrastructure" indicator of the UI GreenMetric World University Rankings, exploring the case of the Universidad Católica de Córdoba (UCC). In an environment where sustainability becomes a transversal axis for university management, the UCC has implemented an environmental conservation strategy of natural resources and management of sustainable infrastructure, demonstrating a firm commitment to caring for the world we live in. Combining the estimation of the institutional carbon footprint, the conservation of the native forest, the promotion of safe, sustainable and accessible infrastructures, and the care of human health, the UCC moves towards sustainability from a comprehensive approach. Its projects linked to environmental care seek a triple impact: 1) Environmental, through the displacement of carbon dioxide (CO2). 2) Academic, instances of training, awareness and research. 3) Social, activities, projects or programs linked to University Social Responsibility. This approach aligns with the spirit of the Encyclical Letter Laudato Si', emphasizing the interconnection between human and social dimensions and environmental conservation. This model involves combining the significant capture of CO2 from our native forest, the execution of the clean energy infrastructure project with low CO2 emissions to mitigate up to 70% of the environmental impact of our carbon footprint. This study contributes to the global dialogue on sustainable practices in the university environment, proposing a replicable framework for other institutions committed to sustainability.